Higher Temperatures, Higher Solar Radiation, and Less Humidity Is Associated With Poor Clinical and Laboratory Outcomes in COVID-19 Patients - Hachim, Mahmood Yaseen; Hachim, Ibrahim Y.; Naeem, Kashif; Hannawi, Haifa; Al Salmi, Issa; Hannawi, Suad (Frontiers in Public Health, 2021)
Background COVID-19 pandemic varies between countries with suggestions that weather might contribute to the transmission mode, disease presentation, severity, and clinical outcomes. Yet, the exact link between climate and COVID-19 is still not well explored. Objectives To evaluate the effect of hot geographical region weather (like UAE) on COVID-19 clinical profile and outcomes. Temperature, wind speed, cloud cover, precipitation, and other weather-related variables were studies in relation to COVID-19 outcomes and laboratory results. Methodology COVID-19 positive patients, a total of 434 admitted between January to June 2020, were recruited from Al Kuwait Hospital, Dubai, UAE. Temperature, wind speed, cloud cover, precipitation rate were recruited from history+ for the day of COVID-19 patients presented to the hospital. After, weather, different parameters were correlated with COVID-19 clinical and laboratory parameters. Results Our results showed that patients admitted in days with higher temperatures, higher solar radiation, and less humidity were associated with higher deaths. This association can be linked to the association of weather parameters with age at diagnosis, higher CRP, neutrophil count, WCC, AST, and ALP, and lower lymphocyte count, eGFR, Hb, Na, and albumin. All of which consider as poor prognostic factors for COVID-19. Conclusion Our study highlighted the importance of weather-related variables on the dynamics of mortality and clinical outcomes of COVID-19. The hot weather might weaken the immune system and unleash an inflammatory response that makes some people, especially those with comorbidities or older ages, more susceptible to infections or to develop aggressive inflammation that ends up with complications and mortality.